THE EFFECT OF PELVIC ROCKING ON PAIN REDUCTION DURING THE FIRST STAGE OF LATENT PHASE LABOR AT POASIA COMMUNITY HEALTH CENTER KENDARI CITY : PELVIC ROCKING ON PAIN REDUCTION - Fety, Yulli; Dina, Hasniah; Rahma, Aghisna Anis (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: The latent phase of the first stage of labor, during the initial period of contractions until the cervix dilates to 3 centimeters, can last approximately 6-12 hours. During this phase, the body starts preparing the cervix to open and widen, allowing the baby to pass through the birth canal.  One method that can be used to reduce labor pain is pelvic rocking. Methods: This study employed a true experimental design using a pretest-posttest group design, involving both an experimental group and a control group. The study population consisted of 56 pregnant women. The research instrument used was a pain assessment observation sheet with the Numeric Rating Scale. Data were analyzed using SPSS. Results: The study showed that, in the experimental group, the average pain level of mothers in the first stage of labor before the intervention was 4.11. After the intervention, which involved pelvic rocking, there was a decrease in the pain scale, with an average pain level of 2.38. In the control group, the pretest pain showed an average pain level of 4.27, while the posttest pain assessment showed an average pain level of 3.83. Based on statistical tests, a p-value (asymp. sig. 2-tailed) of 0.000 < 0.05. Conclusion: This study states that pelvic rocking has an effect on reducing pain during the first stage of labor. It is suggested that a combination therapy be provided to enhance comfort through pain scale reduction.